2021
DOI: 10.1007/s11469-021-00569-0
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Distress, Alexithymia, Dissociation, and Risk of Addiction During the First Wave of COVID-19 in Italy: Results from a Cross-sectional Online Survey on a Non-clinical Adult Sample

Abstract: This study aimed to explore the prevalence of post-traumatic distress, alexithymia, dissociation, and addictive behaviors during the stressful situation of the COVID-19 pandemic. It also aimed to determine whether trauma, alexithymia, and dissociation can effectively predict the risk of addiction in non-clinical subjects during the COVID-19 pandemic. Two hundred nineteen subjects completed a web survey during the first COVID-19 lockdown in Italy, including the Impact of Event Scale-Revised (IES-R), the Dissoci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 45 publications
(69 reference statements)
5
44
1
Order By: Relevance
“…Neurobiological studies have also shown that alexithymia is associated with dysregulated cortisol levels in response to stressful situations [100,101], resulting in higher anxiety and depressive symptoms [102,103]. Higher psychopathological symptoms due to COVID-19 among individuals with high levels of alexithymic have also been shown [61][62][63][64], in line with our findings.…”
Section: Main Findingssupporting
confidence: 88%
See 2 more Smart Citations
“…Neurobiological studies have also shown that alexithymia is associated with dysregulated cortisol levels in response to stressful situations [100,101], resulting in higher anxiety and depressive symptoms [102,103]. Higher psychopathological symptoms due to COVID-19 among individuals with high levels of alexithymic have also been shown [61][62][63][64], in line with our findings.…”
Section: Main Findingssupporting
confidence: 88%
“…Moreover, recent studies have shown the complex relationship between individuals' attachment, alexithymia, and psychopathological difficulties, showing that adolescents' alexithymic traits played a mediation role in the effect of attachment on psychopathological difficulties [69,70]. Overall, findings from international literature have shown the predictive role of attachment on levels of alexithymia [67,68], that in turn predicted psychopathological outcomes resulting from COVID-19 [61][62][63][64]. This evidence suggests that adolescent's attachment could influence psychological responses to the COVID-19 pandemic more directly than via alexithymia.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The COVID-19 pandemic has impacted mental wellbeing disproportionately among specific groups including adolescents, students, women, and healthcare workers, among others (Biviá-Roig et al, 2020;Commodari and La Rosa, 2020;Wang and Zhao, 2020;Tasnim et al, 2021). Moreover, increases in drinking behaviors, problematic use of smartphone, internet, social media, gaming, and other addictive behaviors have been reported during the pandemic (Higuchi et al, 2020;Islam et al, 2020e, 2021e;Rodriguez et al, 2020;La Rosa et al, 2021). These addictive behaviors may be linked to pandemic-related traumatic events (e.g., lockdowns) and have been associated with mental health concerns including anxiety and depression (Higuchi et al, 2020;Rodriguez et al, 2020;Islam et al, 2021e;La Rosa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increases in drinking behaviors, problematic use of smartphone, internet, social media, gaming, and other addictive behaviors have been reported during the pandemic (Higuchi et al, 2020;Islam et al, 2020e, 2021e;Rodriguez et al, 2020;La Rosa et al, 2021). These addictive behaviors may be linked to pandemic-related traumatic events (e.g., lockdowns) and have been associated with mental health concerns including anxiety and depression (Higuchi et al, 2020;Rodriguez et al, 2020;Islam et al, 2021e;La Rosa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%